EFEKTIVITAS KOORDINASI ANTARINSTANSI PADA PELAKSANAAN PROGRAM MAKAN BERGIZI GRATIS KOTA SEMARANG - Nonik Erica Deviana; Candra Yudha Satriya (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2026)
The Free Nutritious Meals Program involves multiple agencies with different mandates, making coordination effectiveness essential for distribution, food safety, data alignment, and problem resolution. This study analyses the effectiveness of interagency coordination in implementing the program in Semarang City. A descriptive qualitative approach was employed. Data were collected through interviews with five informants from the Semarang City Health Office, Education Office, Nutrition Fulfilment Service Office, Kedungmundu 2 Nutrition Fulfilment Service Unit, and Kedungmundu Elementary School, supported by observations at the five sites. The findings show that coordination is reasonably effective in the operational relationship between the service unit and school and in the command flow between the regional nutrition office and service unit. Effectiveness is supported by relatively clear role distribution, WhatsApp communication, meetings, official letters, telephone communication, and task-force forums. Coordination is not yet fully effective across agencies because evaluation schedules are inconsistent, SI-MANGGIS use is uneven, data synchronization problems remain, and schools do not consistently receive direct communication from relevant offices. Improvement requires monthly evaluation forums, integrated data management, wider promotion of digital channels, joint field monitoring, and continuous food-safety capacity building.